HIV Preexposure Prophylaxis as a Gateway to Primary Care - Marcus, Julia L. (Am J Public Health, 2018)
Objectives. To determine whether HIV preexposure prophylaxis (PrEP) use is associated with use of non–HIV-related health care. Methods. We conducted a cross-sectional study of potential PrEP candidates at a Boston, Massachusetts, community health clinic during 2012 to 2016, comparing the proportion of PrEP users and non-PrEP users receiving primary care. Results. Of 5857 PrEP candidates, 2047 (35%) were prescribed PrEP. After adjustment for demographics and number of visits, more PrEP users received influenza vaccination (prevalence ratio [PR] = 1.28; 95% confidence interval [CI] = 1.20, 1.37), tobacco screening (PR = 1.06; 95% CI = 1.02, 1.09), and depression screening (PR = 1.07; 95% CI = 1.04, 1.11) compared with non-PrEP users. After additional adjustment for diabetes, hypertension, and overweight or obesity, more PrEP users received glucose testing (PR = 1.64; 95% CI = 1.56, 1.72) but fewer received hemoglobin A1c testing (PR = 0.81; 95% CI = 0.71, 0.93) compared with non-PrEP users. Conclusions. PrEP use was associated with receipt of influenza vaccination, tobacco and depression screening, and glucose but not hemoglobin A1c testing. Among PrEP users receiving routine care, the benefits of PrEP may extend to behavioral health, mental health, and prevention and treatment of other infectious and chronic diseases.